Vicissitudes of simultaneous death: In case of the death of father and son, do the grandchildren inherit the grandparent? - Mendoza Vásquez, Enrique (2018)
In this article, the author studies the vicissitudes of simultaneous death of father and son. The interpretations of Article 62 of the Civil Code have resulted in two contradictory positions, in doctrine and jurisprudence. The question proposed is if grandchildren have a right or not to the inheritance of the grandparent, who has dead at the same time as his father. This is the subject analyzed in this paper. Interpretation oriented by values underlying Law, whose aim is Justice, is preferred.